Efficient Peer-to-Peer Content Sharing for Learning in Virtual Worlds - Bingqing Shen; Jingzhi Guo (Journal of Universal Computer Science, 2019)
Virtual world technologies provide new and immersive space for learning, training, and education. They are enabled by the content creation and content sharing function for allowing users to create and interoperate various learning objects. Unfortunately, virtual world content sharing based on persistent virtual world content storage, to the best of our knowledge, does not exist. In this paper, we address this problem by proposing a content sharing scheme based on Virtual Net, a virtual world persistency framework. For efficient content retrieval, three strategies have been proposed to reduce communication overhead and content load delay. By integrating these strategies, a virtual world content search and retrieval algorithm has been devised. The experiment results verify the effectiveness of the algorithm.